Duration of Maternity Leave in Germany: A Case Study of Nonparametric Hazard Models and Penalized Splines - Torben Kuhlenkasper; Göran Kauermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The paper investigates maternity leave behavior in West Germany for females being employed between 1995 and 2006 using data from the German Socio Economic Panel. The observational study focuses on the investigation of individual and family-related covariate effects on the duration of maternity leave following first or second childbirth, respectively. Dynamic duration time models are used in which covariate effects are allowed to vary smoothly with duration of being in maternity leave. The intention of the paper is to demonstrate with state of the art models how effects of covariables change over time and to analyse substantial differences between maternity leaves following first and second childbirth. Particularly the personal income of mothers and the educational attainment influence the decision when to return into employment. The leave period following second birth is influenced by the mothers' attachment to the labour market between their two maternity leave periods. As fitting routine penalized spline smoothing effects is employed using available software in R (www.r-project.org).
Keywords: C14; C23; C41; J13; J24; J60; 330; Duration time models; dynamic effects; maternity leave; Panel data; employment transition